1999
DOI: 10.1139/f99-209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of habitat use on PCB body burden in Hudson River striped bass (Morone saxatilis)

Abstract: The Hudson River commercial striped bass (Morone saxatilis) fishery has been closed since 1976 due to high polychlorinated biphenyl (PCB) contamination. Accurate forecasting of PCB levels in striped bass has been confounded by high variance in contamination among individuals. We investigated the relationship between habitat use and PCB contamination in Hudson River and Long Island Sound striped bass using electron microanalysis of otolith strontium to generate time series of individual salinity habitation. Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…1). Contingents of striped bass were initially classified on the basis of visual inspection of salinity chronologies (Zlokovitz & Secor 1999). Mean lifetime salinity (the mean of all salinity records from transect points for an individual) corroborated these classifications (Table 1).…”
Section: Collectionsmentioning
confidence: 91%
See 2 more Smart Citations
“…1). Contingents of striped bass were initially classified on the basis of visual inspection of salinity chronologies (Zlokovitz & Secor 1999). Mean lifetime salinity (the mean of all salinity records from transect points for an individual) corroborated these classifications (Table 1).…”
Section: Collectionsmentioning
confidence: 91%
“…Migrations within populations are affected by changes in population abundance, climate, flow regimes, and degradation of migration corridors (Leggett 1977). Variable migrations result in differential vulnerability to exploitation and habitat degradation (Kohlenstein 1981, Limburg & Schmidt 1990, Rose & Leggett 1991Frank 1992, Fogarty 1998, Zlokovitz & Secor 1999. Measuring migration variability within populations is complex because methodologies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Clark (1968) described 2 striped bass contingents in the Hudson River estuary: one that would migrate annually from the river to coastal habitats and another comprised of individuals that were spawned in the river and never left. Secor et al (2001) have since observed 3 contingents in the same population, and the migration patterns of these contingents have been used to explain individual variability in PCB (polychlorinated biphenyl) contamination of striped bass in the Hudson River (Zlokovitz & Secor 1999, Ashley et al 2000, Zlokovitz et al 2003. Another example of population contingents is seen in Japanese eels.…”
Section: Abstract: Population Contingents · Estuarine-dependency · Omentioning
confidence: 99%
“…McLaren et al (1981) also described separate migration behaviors in which one group begins a coastal migration after spawning and the other remains resident in the river. Recent otolith microchemistry studies have verified this migratory behavior and classified three contingents: (1) a resident contingent that inhabits the freshwater and oligohaline tidal portion of the Hudson River; (2) an estuarine contingent that inhabits the lower estuary, including the New York City harbor and western Long Island Sound regions; and (3) a migratory contingent that inhabits marine environments and makes annual excursions into freshwater for spawning (from here on, contingents will be labeled ''resident,'' ''estuarine,'' and ''migratory'' after Zlokovitz and Secor 1999, Secor et al 2001, and Zlokovitz et al 2003). …”
mentioning
confidence: 99%